Development of the investment and construction sectors of the economy in the context of digitalisation (ARTEKS : Jurnal Teknik Arsitektur, 2025)
The construction industry plays a key role in infrastructure development and economic growth, especially in the Asia-Pacific region (APAC), where almost half of the world’s construction is expected to be concentrated by 2030. Investment activity in this region, thanks to digitalization, helps to optimize design, construction management, and financing processes, which increases the market’s attractiveness to international investors. Given this, digital transformation is a determining factor in improving the efficiency, safety, and environmental friendliness of the industry, which necessitates a study of its impact on businesses. The purpose of this research article is to analyze the level of digitalization of the construction industry, assess the main barriers and prospects for the introduction of digital technologies, and determine their impact on the productivity of enterprises. The study is based on general scientific methods of cognition, including the synthesis of literature sources, methods of generalization and systematization, analysis of statistical data and comparison of the results of regression analysis of the relationship between the level of digitalization and key performance indicators of enterprises for the period 2024-2025. Given that digitalization contributes to increasing productivity, quality of construction, investment attractiveness and economic efficiency of enterprises; it was found that the main trends are the growth of the use of 3D printing (39%), artificial intelligence (37%), the Internet of Things (45%) and cloud software (49%); at the same time, barriers are high costs (54%), lack of digital skills (54%) and low level of staff adaptation to innovation (51%). Digital transformation is a strategic imperative for the construction industry to ensure competitiveness and sustainable development. Successful implementation of digital technologies depends on the elimination of financial, organizational and personnel barriers, as well as on the consistency of digital solutions with the overall strategy of enterprises.
Keywords: Artificial intelligence; Cloud technologies; Construction industry; Digital transformation; Digitalization; Investments; Productivity